Beach Nourishment as an Adaptation to Future Sandy Beach Loss Owing to Sea-Level Rise in Thailand - Chatuphorn Somphong; Keiko Udo; Sompratana Ritphring; Hiroaki Shirakawa (Journal of Marine Science and Engineering, 2020)
A recent study suggested that significant beach loss may take place on the coasts of Thailand by the end of the 21st century as per projections of sea-level rise by the Intergovernmental Panel on Climate Change (IPCC). The present study adapts a framework and provides broad estimations for sand volumes and costs required to apply beach nourishment to each coastal zone in Thailand using a technique based on the Bruun rule assumption. Results indicate that a minimum of USD 2981 million (the best scenario) to a maximum of USD 11,409 million (the worst scenario) would be required to maintain all sandy beaches at their present width. Further, the effect of filling particle size on beach nourishment was analyzed in this study. The cost of beach nourishment ranges between USD 1983 and 14,208 million when considering filling particle size diameters of 0.5 and 0.2 mm. A zonal sand volume map for all 51 sandy beach zones in Thailand was created for use as an overview to help decision makers develop a more feasible adaptation plan to deal with the future sea-level rise for Thailand.